Profitability in Indonesia Manufacturing: Case Study on Automotive and Component Sector - Rimadhani, Risthia Hanesty; Siagian, Bekman (Formosa Journal of Sustainable Research, 2024)
This study aims to analyze and measure the extent to which liquidity ratio, firm’s size, gearing ratio and market share affect the profitability on Indonesia manufacturing, case study with automobiles and components sector. The research method uses quantitative research with saturated samples 10 companies and the financial year period 2015-2020. Panel regression with common model effect regression analysed by Eviews10 software. This study show that liquidity ratio has a significant positive effect on profitability (proxy by return on assets, net profit margin and gross profit margin). Leverage with gearing ratio has a significant negative effect on profitability (proxied by net profit margin), while company size and market share have an effect on profitability, with smaller significance probability